PENGARUH JENIS ELEKTRODA TERHADAP SIFAT MEKANIK HASIL PENGELASAN SMAW MATERIAL BAJA ST 42 - Armika, I Putu; Nugraha, I Nyoman Pasek; Widayana, Gede (Otopro, 2025)
SMAW (Shield Metal Arc Welding) is an activity carried out in the joining process which has a metal base material. The purpose of the study was to analyze the tensile strength results, and to determine the microstructure of the strongest electrode. using three types of electrodes RB-26, RD-250 and LB-52U electrode diameter 2.6mm on ST37 steel plate with ASTM E8 specimens with a length of 200mm, a width of 20mm and a thickness of 3mm. SMAW welding process with a welding current of 95A, with a position of 1G (flat). This study uses a descriptive quantitative statistical data processing method of experiments using Microsoft Excel software. From the results of the study there is a significant influence on the tensile strength of the three electrode variations. The highest tensile strength results are shown in the RD-260 electrode with a tensile strength of 513.28MPa and the lowest is the LB-260 electrode with a tensile strength of 478.09MPa. The results of microstructure testing with 200x and 400x measurements show that pearlite is the most abundant in the RB-26 electrode and ferrite is the most abundant in the RD-260 electrode. From the tensile test and microstructure test, there is a mutually influencing relationship that the highest tensile strength is the RD-260 electrode type, proven by the greater dominance of ferrite which is softer and more ductile. This finding indicates that the selection of electrode type plays an important role in determining the mechanical properties of the welding results.